Craniofacial Morphology and Upper Airway Dimensions in Patients with Hypermobile Ehlers-Danlos Syndrome Compared to Healthy Controls - Liselotte Sonnesen; Tessie Pawlik; Eva Fejerskov Lauridsen (Stilus Optimus, 2021)
Objectives: The aims of the present case-control study were to compare craniofacial morphology, airway minimum cross-sectional area and airway volume between patients with hypermobile Ehlers-Danlos syndrome and healthy controls. Material and Methods: The sample comprised 18 hypermobile Ehlers-Danlos syndrome (hEDS) patients (16 females, 2 males, mean age 34.1 [SD 10.35] years), clinically diagnosed and genetically tested in order to exclude other types of EDS, and 16 controls (14 females, 2 males, mean age 37.9 [SD 10.87] years) with neutral occlusion and normal craniofacial morphology. Craniofacial morphology was assessed on lateral cephalograms. Minimum cross-sectional area and upper airway volume were assessed on cone-beam computed tomography and analysed by standard and well-validated methods. Differences were tested by logistic regression analysis adjusted for age, gender and body mass index (BMI). Results: No significant differences in craniofacial morphology were found between hEDS patients and controls. Airway minimum cross-sectional area (P = 0.019) and airway volume (P = 0.044) were significantly smaller in hEDS patients compared to controls. When adjusted for age, gender and BMI no significant differences were found. However, minimum cross-sectional area was almost significant (P = 0.077). Conclusions: The craniofacial morphology and airway dimensions of hypermobile Ehlers-Danlos syndrome patients were comparable to controls, with a tendency towards a smaller minimum cross-sectional area in the hypermobile Ehlers-Danlos syndrome group. The results may prove valuable for understanding the effect of hypermobile Ehlers-Danlos syndrome on craniofacial morphology and the upper airways.